After the German November Revolution 1918: The Compromise on Religious Instruction in Elementary Schools in the Weimar Constitution - Hein Retter (International Dialogues on Education: Past and Present, 2018)
A tiny section on the agenda of the National Assembly of the Weimar Republic from February to July, 1919 was entitled ‟Religious instruction and the public elementary school”, part of the preparation for the new Constitution of the German Reich, the so-called Weimar Constitution [Weimarer Reichsverfassung; abbr. WRV], of August 11th, 1919. The three democratic parties, the moderate-socialist SPD, the Catholic Zentrum Party and the liberal-democrat DDP, were the political mainstays of the Weimar Republic, which existed from 1919 to 1933. But these three parties had absolutely different ideologies concerning the role of religion in public education, especially in the elementary school (Volksschule), the lower school system. While the topic ‘religion and school’ in the Weimar Constitution has been often presented from a politically leftish point of view in the past, here, following the principle of a plurality of historical perspectives, the interests of the Catholic Zentrum Party will be more strongly focussed upon. I would like to also show how difficult the circumstances were that eventually led to an agreement regarding the school articles of the Weimar Constitution. Article 146(1) WRV required a national school act which was to be the framework for further educational laws of the ‘Länder’ (states). All political attempts failed to produce such a national law (Reichsschulgesetz) during the era of the Weimar Republic (in the interest of standardization of state education) because of different policies in the ‘Reich’ and the ‘Länder’ (which were responsible for school education and its legal basis). Just like the parties’ differences in school policy could not be bridged in the years after establishing the Constitution of 1919.